1973
DOI: 10.1126/science.181.4099.557
|View full text |Cite
|
Sign up to set email alerts
|

Phase Transitions and Heterogeneity in Lipid Bilayers

Abstract: The optical reflectivity of several well-characterized lipid bilayer systems has been correlated with calorimetric studies of the membrane components. There is a large increase in mean membrane thickness when a bilayer is cooled below the transition temperature of the membrane lipid. Similar studies on membranes generated from a mixture of two lipids possessing different degrees of unsaturation suggest that between the characteristic transition temperatures of the two lipids, the bilayer contains clusters of g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
31
0

Year Published

1974
1974
2004
2004

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(35 citation statements)
references
References 7 publications
4
31
0
Order By: Relevance
“…It is well known that the properties of allosteric enzymes can be influenced by compounds unrelated to the specific substrate, and allosteric adrenoceptors could appropriately be influenced by the 'modulator' substance that has been reported to alter the balance of a-and fl-adrenoceptor components of responses of skeletal muscle blood vessels of dogs (Szentivanyi, Kunos & Juhasz-Nagy, 1970) and by thyroid hormone (Kunos, Vermes-Kunos & Nickerson, 1974). The physical state of membrane lipids is also temperature dependent (Pagano, Cherry & Chapman, 1973), and such a change within the critical temperature range could either alter directly the interaction of POB with the receptors or trigger an alteration of membrane receptor protein.…”
Section: Effects Of Phentolamine On Block By and Binding Of [3h]pobmentioning
confidence: 99%
“…It is well known that the properties of allosteric enzymes can be influenced by compounds unrelated to the specific substrate, and allosteric adrenoceptors could appropriately be influenced by the 'modulator' substance that has been reported to alter the balance of a-and fl-adrenoceptor components of responses of skeletal muscle blood vessels of dogs (Szentivanyi, Kunos & Juhasz-Nagy, 1970) and by thyroid hormone (Kunos, Vermes-Kunos & Nickerson, 1974). The physical state of membrane lipids is also temperature dependent (Pagano, Cherry & Chapman, 1973), and such a change within the critical temperature range could either alter directly the interaction of POB with the receptors or trigger an alteration of membrane receptor protein.…”
Section: Effects Of Phentolamine On Block By and Binding Of [3h]pobmentioning
confidence: 99%
“…In artificial membranes these changes have generally been described as phase transitions, implying that an entire membrane changes from fluid (liquid-crystal) to solid (gel phase) over a narrow temperature range. However, phase changes especially in membranes of mixed lipid species have been discussed in terms of phase separations, rather than as phase transitions (2,3). It has been suggested that several transition temperatures can be defined in mixed lipid membranes, in which classes of lipid molecules coaggregate and solidify when a membrane is cooled, leaving other lipids, with lower melting temperatures still fluid.…”
mentioning
confidence: 99%
“…Membranes were formed from a 1,2-distearoyl-glycero-3-phosphocholine/decane solution. There is also a paper, based on optical reflectivity measurements on membranes from monostearoylglycerol in n-hexadecane, which demonstrated an ;70% increase in membrane thickness when the system was cooled below the tc of 55°C (8).…”
mentioning
confidence: 99%